Toxicity of nanoemulsion formulations of neem oil against Spodoptera litura (F.) - Jupery, Nurul Athirah (2016)
Spodoptera litura (Lepidoptera :Noctuidae) commonly known as armyworm, is one of the most important insect pests of agricultural crops in the Asian tropics. This noctuid is widely distributed throughout tropical and temperate Asia, Australia and the Pacific Islands. Their larvae are polyphagous defoliators as well as may damage tubers and roots. The extensive damage on crops has given tremendous economic impact on agricultural industry and reduces farmer’s income. Insecticides application is a popular method to solve this problem. Neem oil is one of the environmental-friendly insecticides. Thus, this research was conducted to investigate the effect of formulated neem extracts on mortality of S.litura and to determine the feeding consumption of S.litura after being treated with neem formulations. The leaf dipping method was used with minimum of five treatments including control. Each treatment was replicated five times and a minimum of five third instar larvae were used for each treatment. Mortality of larva was recorded at 24, 48 and 72 hour after treatment (HAT) and the data were subjected to ANOVA by using SARS program. The LC50 value was obtained by probit analysis. For determination of antifeedant activity of larvae, it was recorded at 24 HAT and the data were subjected to ANOVA by using SARS program. Nanoemulsion formulation 2 was the best formulation because it caused high mortality of third instar larvae of S.litura at all treatments. It also has high antifeedant activity towards S.litura compared to other formulations.